2024
DOI: 10.1111/nph.19635
|View full text |Cite
|
Sign up to set email alerts
|

Drought increases Norway spruce susceptibility to the Eurasian spruce bark beetle and its associated fungi

Sigrid Netherer,
Linda Lehmanski,
Albert Bachlehner
et al.

Abstract: Summary Drought affects the complex interactions between Norway spruce, the bark beetle Ips typographus and associated microorganisms. We investigated the interplay of tree water status, defense and carbohydrate reserves with the incidence of bark beetle attack and infection of associated fungi in mature spruce trees. We installed roofs to induce a 2‐yr moderate drought in a managed spruce stand to examine a maximum of 10 roof and 10 control trees for resin flow (RF), predawn twig water potentials, terpene, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…As reported by Matović et al [31] and Stojanović et al [33], in those years, there was a huge outbreak of I. typographus and P. chalcographus, which, at that moment, acted like a primary pest. However, it should be taken into account that bark beetle outbreaks in Norway spruce forests are a consequence of adverse climatic effects, such as drought, as their defensive mechanisms are weakened when affected by summer drought [115][116][117][118]. Spatial-temporal expansion of forest glades in 2015, 2016, and 2017, which previously emerged over small areas in 2014 (Figure 3 and Table 4), clearly indicate bark beetle activity.…”
Section: Forest Cover Lossmentioning
confidence: 97%
“…As reported by Matović et al [31] and Stojanović et al [33], in those years, there was a huge outbreak of I. typographus and P. chalcographus, which, at that moment, acted like a primary pest. However, it should be taken into account that bark beetle outbreaks in Norway spruce forests are a consequence of adverse climatic effects, such as drought, as their defensive mechanisms are weakened when affected by summer drought [115][116][117][118]. Spatial-temporal expansion of forest glades in 2015, 2016, and 2017, which previously emerged over small areas in 2014 (Figure 3 and Table 4), clearly indicate bark beetle activity.…”
Section: Forest Cover Lossmentioning
confidence: 97%
“…However, their high cost was a limiting factor in the framework of this study. Considering that other factors, such as stand and terrain characteristics, play a significant role in Norway's spruce dieback [28,31,118], future analyses should include these factors. This can be achieved by employing machine learning methods to provide more accurate and reliable results.…”
Section: Methodological Limitations Of the Used Methodology In Detect...mentioning
confidence: 99%
“…Worth noticing is the large effect of the pre-drought (2009) results of the EVI, SAVI, TCG, and TCW in predicting the forest cover loss in 2015, as such a state points to pre-drought differences, and possibly the susceptibility of different Norway spruce populations, or their respective habitats, to drought events in the Kopaonik NP. The cause of this may be found in the research of Rehschuh et al [118], in which they reported that Norway spruce trees growing on shallow, well-drained soil expressed a relatively higher drought sensitivity compared to trees from a site with deep, silty soil. The practically non-existent ability to predict the forest cover loss in 2015, with the post-drought data (2013 and 2014) using the NDVI and its modified version TVI, should not be considered unusual.…”
Section: Evaluation Of VI Sensitivity In Detecting Responses To Droug...mentioning
confidence: 99%
“…1A). Host tree-bark beetle interaction is generally considered multifaceted, and various factors across different spatial and temporal scales shape their interactions (Jakuš et al 2011;Kautz et al 2011;Netherer et al 2024). Furthermore, Ips typographus shows density-dependent host colonization behaviour.…”
Section: Eurasian Spruce Bark Beetle Ecologymentioning
confidence: 99%